MANAJEMEN SUMBER BELAJAR PENDIDIKAN DAN SISTEM INFORMASI MANAJEMEN PENDIDIKAN - Hadiwijaya; salsabila, safira; Muh.Arif Hidayatullah; Sartika Sari; Anisa Safitri; Sulkifli (As-Sulthan Journal of Education, 2025)
Educational management is an imperative component in achieving effective and efficient learning goals. One important aspect in educational management is classroom and student management, which plays a direct role in creating a conducive learning environment. This article discusses the concept, principles, and application of classroom management and student management in the context of formal education. This study uses a descriptive qualitative approach with literature studies as a method of collecting information. The results of the study indicate that effective classroom management includes spatial planning, time management, and clear rule enforcement, while student management involves understanding individual characteristics, providing motivation, and an individual approach to guidance. The conclusion of this study confirms that the synergy between classroom management and students can improve the quality of learning and encourage the achievement of ideal learning outcomes.